The collapse of rural order in Ottoman Anatolia : Amasya 1576-1643 - Özel, Oktay. (The Ottoman Empire and its Heritage, 2016)
Did the 'seventeenth-century crisis' visit the Ottoman Empire? How can we situate the explosion of rural violence and the rebellions of the turn of the seventeenth century in the Anatolian countryside? The Collapse of Rural Order in Ottoman Anatolia provides the reader with a fresh and innovative perspective on the long scholarly debate over the question of 'decline' in early modern Ottoman history. It offers a new agenda, new type of source material, and a new methodology for the study of demographic crisis. Through a systematic examination of little-known detailed avârız registers, Oktay Özel demonstrates in detail the mass desertion of rural settlements, the destruction of agricultural economy, and the resulting collapse of rural order in Ottoman Anatolia at the turn of the seventeenth century.